Geographies of transport I: Reinventing a field? - Schwanen, T (SAGE Publications, 2015)
© 2015, © The Author(s) 2015. This first of three reports confirms and extends recent reflections on the diversity and vibrancy of the study of transport in geography. It identifies multiple drivers for the recent re-engagement with transport, suggesting that the way in which transport has become enmeshed with other forms of flow and circulation across multiple spatial and temporal scales may be the most significant. It reviews recent geographical research on the enmeshment of transport and a wide range of other circulations in three settings: the economy, climate change, and public health. The review suggests that the now widespread attention to transport issues by geographers who may not self-identify as experts in transport or mobilities is the defining characteristic of recent work on the geographies of transport. The re-engagement from across the discipline is potentially reinventing the field by bringing an unprecedented variety of perspectives to bear on the geographical analysis of transport. It means that the transport geography community should not limit its attention to staging further dialogue with the mobilities community but rather strike up more topic-oriented conversations across the whole discipline.